Large optical nonlinearities of conjugated porphyrin polymers in the near infrared - Hales, J; Cozzuol, M; Screen, T; Anderson, H; Perry, J (2008)
The optical nonlinearities of porphyrin polymers were investigated in the telecommunications band: large values, slow kinetics in solutions revealed efficient optical limiting while large values, fast kinetics in films suggested ultrafast applications should be possible. © 2008 Optical Society of America.